2019
DOI: 10.1039/c9qi00730j
|View full text |Cite
|
Sign up to set email alerts
|

Tunable photochromic properties of hybrid solids controlled by the conjugated length of non-photochromic units

Abstract: The photochromic performance of two hybrid zincophosphite frames could be tuned via enlarging the conjugated length of the non-photochromic bipyridine unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…After irradiation, the energy of phen is given to adjoining BTA 3− , resulting in the ET from O carboxylate to N phen . Thus, the photocoloration of 1 can be interpreted as photoinduced ligand‐to‐ligand ET, which also determines the photochromism of other reported CHPMs [45–53] . To assure the adequate photoactivation for ET for the following characterisations, the irradiation time was enlarged to 120 min for obtaining the colored sample ( 1P ).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…After irradiation, the energy of phen is given to adjoining BTA 3− , resulting in the ET from O carboxylate to N phen . Thus, the photocoloration of 1 can be interpreted as photoinduced ligand‐to‐ligand ET, which also determines the photochromism of other reported CHPMs [45–53] . To assure the adequate photoactivation for ET for the following characterisations, the irradiation time was enlarged to 120 min for obtaining the colored sample ( 1P ).…”
Section: Figurementioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30] Besides the CHPMs based on photodeformable or photoresponsive ligands, the conjugated N-heterocycle moieties as potential electron acceptors (EAs) are also desirable units for yielding CHPMs. [41][42][43][44][45][46][47][48][49][50] The assembly of various EAs moieties, electron donors (EDs) species, and metal ions generates assorted CHPMs driven by photoinduced electron-transfer (ET) between EDs and EAs, [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] and the resulting CHPMs feature additional fascinating photoresponsive functionality like photomagnetism, photocurrent, sensor for X-ray, etc. [41][42][43][44][45][46][47][48][49][50]…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Recently,w ea nd others have reportedt hat the introductiono fp olypyridine-derivative moieties to metal phosphite systemsp rovides possibilities to construct CHPMs. [11] Further structure-propertyr elationship analysis revealed that the LLET between phosphite and polypyridine-derivative is responsible fort he resultant photochromism. In other words, the polypyridine derivative could act as ap otential p-EA to promote the resultant ET in the presence of suitable ED ligand.…”
Section: Introductionmentioning
confidence: 99%